2020
DOI: 10.1111/cup.13769
|View full text |Cite
|
Sign up to set email alerts
|

PAS and GMS utility in dermatopathology: Review of the current medical literature

Abstract: The American Society of Dermatopathology has established an Appropriate Use Criteria (AUC) Committee with the intention of establishing evidence-based recommendations regarding the appropriateness of various ancillary tests commonly utilized by dermatopathologists. Periodic acid Schiff (PAS) and Grocott (or Gomori) methenamine silver (GMS) stains represent some of the most commonly employed ancillary tests in dermatopathology. The utility of these tests was targeted for evaluation by the AUC. This literature r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Our results support pre‐ordering PAS or GMS for onychomycosis in nail clippings, which is not surprising given the superior sensitivity of the stains over H&E in nail clippings submitted to rule out onychomycosis. One difference between these stains is that GMS highlights living and dead organisms, whereas only viable organisms are highlighted by PAS 10,28 ; our results did not indicate an attributable difference between these stains, likely because of limitations in the methodology employed to develop the AUC where tests are considered independently. Although one might favor the superior absolute sensitivity of GMS, detecting only viable organisms (ie, by using PAS) might be more clinically relevant.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Our results support pre‐ordering PAS or GMS for onychomycosis in nail clippings, which is not surprising given the superior sensitivity of the stains over H&E in nail clippings submitted to rule out onychomycosis. One difference between these stains is that GMS highlights living and dead organisms, whereas only viable organisms are highlighted by PAS 10,28 ; our results did not indicate an attributable difference between these stains, likely because of limitations in the methodology employed to develop the AUC where tests are considered independently. Although one might favor the superior absolute sensitivity of GMS, detecting only viable organisms (ie, by using PAS) might be more clinically relevant.…”
Section: Discussionmentioning
confidence: 63%
“…The other subgroup selected Gömöri methenamine silver (GMS; Grocott‐Gömöri) and periodic acid‐Schiff (PAS) stains for AUC development. Review and analysis of the literature (from 1957 to May 2019) was reported by Shalin et al 10 Twenty‐eight clinical scenarios were rated with 16 of these rated for PAS and GMS (44 total ratings). Consensus by panel raters was reached in 31 of 44 clinical scenarios (70%) scenarios, with over 50% rated “usually appropriate” or “majority usually appropriate.” The ratings for GMS and PAS stains in identical scenarios were largely the same.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special stainings, such as the periodic acid–Schiff stain, are capable of detecting polysaccarides and glycoproteins of the fungal cell wall; the Grocott–Gomori methenamine silver stain that targets carbohydrates is also used in histopathology [ 64 , 75 , 76 , 77 , 78 , 79 ]. The use of stains with fluorescent brighteners can increase sensitivity [ 27 ].…”
Section: Diagnosis Of Invasive Candidiasismentioning
confidence: 99%